1997
DOI: 10.1007/bf01627970
|View full text |Cite
|
Sign up to set email alerts
|

The influence of senescence on craniofacial and cervical morphology in humans

Abstract: This study discusses the morphologic evolution of the cranio-facial and cervical bone structures throughout life. A cephalometric study was made on lateral radiographs. The population studied included 84 males and 102 females. Ages ranged from 21 to 101. The cranial structures, superior facial structure, mandible and cervical vertebral column were successively examined. The anteroposterior diameter of the calvarium does not seem to undergo any modification during life. On the other hand, a highly significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Although senescence has a general effect on the skeleton and specifically on the morphology of the mandible (Doual et al 1997), the size of the mandibular angle in our adult sample did not change with age per se. This is in agreement with the findings of some other researchers (e.g., Keen, 1945;Israel, 1973) although there is no general consensus in the literature on this matter.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Although senescence has a general effect on the skeleton and specifically on the morphology of the mandible (Doual et al 1997), the size of the mandibular angle in our adult sample did not change with age per se. This is in agreement with the findings of some other researchers (e.g., Keen, 1945;Israel, 1973) although there is no general consensus in the literature on this matter.…”
Section: Discussionmentioning
confidence: 48%
“…Most of the previous metrical studies on the mandibular angle have been done on radiographs (Israel, 1973;Doual et al, 1997;Ohm and Silness, 1999;Xie and Ainamo, 2004;Merrot et al, 2005). Ruff (1980) demonstrated that increases in the gonial angle with age are underestimated on lateral radiographs if bigonial breadth also increases.…”
Section: Discussionmentioning
confidence: 98%
“…Increases in craniofacial dimensions such as facial height, mandibular length, bizygomatic and bigonial breadth, and head circumference, length, and breadth have been detected with advancing age (e.g., Pfitzner, 1899;Hellman, 1927;Hrdlička, 1936; Hooten and Dupertuis, 1951;Thompson and Kendrick, 1964;Forsberg, 1979;Ruff, 1980;Behrents, 1985;Forsberg et al, 1991;Bartlett et al, 1992;Bishara et al, 1994;West and McNamara, 1999;Akgü l and Toygar, 2002). Cranial (Humphrey, 1858;Todd, 1924; Israel, 1973a, b;Behrents, 1985;Doual et al, 1997) and mandibular cortical bone thickness (Israel, 1969;Lestrel et al, 1980) have also been found to increase with age. Furthermore, contourrelated studies of the orbits and maxilla suggest these regions undergo age-related differential enlargement (Zadoo and Pessa, 2000;Pessa and Chen, 2002;Shaw and Kahn, 2007).…”
mentioning
confidence: 96%
“…42 In these studies age was not considered as a confounding factor, but the fact is that with age lordosis increases. 54 It was hypothesized that jaw posture may influence muscles and cause postural adaptations at spine level. Unilateral cross-bite has been investigated as a risk factor for asymmetric jaw growth and unbalanced muscle activity.…”
Section: The Role Of Posturementioning
confidence: 99%